(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2024)
Refers to the field reality for integrated manufacturing in Iraq, it needs to be developed Production efficiency in order to improve the quality level, reduce defects and errors, and control time and cost, there is a need to apply effective methods in this field. The goal of this study is to develop performance and improve quality integrated manufacturing by improving performance manufacturing resource planning systems in the hierarchical structure that begins with the institution, factory, cell, and production field, and implementation works manufacturing through line, star, tree, ring, controller area network For the purpose of achieving the objective of the study, the researchers relied first on the comprehensive theoretical study of the concepts of integrated manufacturing, and secondly on the field study carried out by the researchers by conducting an open questionnaire , we have been able to design a closed questionnaire based on 426 questionnaires.